Should Schools be Smaller? The Size-Performance Relationship in relation to Tanzania ' s Advanced Certificate of Secondary Education Results of 2004 to 2009 - Mbamba, Ulingeta O.L. (Papers in Education and Development, 2018)
The study explored whether students in advanced certificate of secondary education perform better, in small, medium or large schools. Using data from 2004 to 2009 examination results of advanced certificate of secondary education published by the National Examinations Council of Tanzania and the use of analysis of variance as well as chi-square tests indicate that there are significant differences in terms of performance in different school sizes, where small schools perform better than medium or large schools. Furthermore, the performed analyses show that there is an association between school size and performance. The same results were obtained when the analysis were done by years of study and subject combinations. The study recommends having small schools in order to improve students ' performance.